2019
DOI: 10.1193/030918eqs052m
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Catastrophe Bonds for Tsunamis: CAT-in-a-Box Trigger and Intensity-Based Index Trigger Methods

Abstract: This study presents a calibration of CAT-in-a-Box and intensity-based index trigger mechanisms for parametric tsunami catastrophe bonds. Trigger conditions for the former are based on fundamental event characteristics, such as earthquake location and magnitude, whereas those for the latter utilize tsunami wave height measurements at a series of observation stations. These solutions are illustrated for a building portfolio in Iwanuma City in Miyagi Prefecture, Japan, by considering a new seafloor observation ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…These are consistent with dominant contributions of the tsunami loss to the total multi-hazard loss at these large trigger levels. It is also noteworthy that these reduced trigger errors are consistent with the results for the tsunami CAT bond trigger design by Goda et al (2019).…”
Section: Station-intensity-based Bond Triggersupporting
confidence: 84%
See 2 more Smart Citations
“…These are consistent with dominant contributions of the tsunami loss to the total multi-hazard loss at these large trigger levels. It is also noteworthy that these reduced trigger errors are consistent with the results for the tsunami CAT bond trigger design by Goda et al (2019).…”
Section: Station-intensity-based Bond Triggersupporting
confidence: 84%
“…A case-study example is focused upon wooden buildings in Miyagi Prefecture, Japan. Because details of the shaking-tsunami catastrophe model and the trigger design methods are explained in Goda and De Risi (2018) and Goda et al (2019), respectively, descriptions of these model and methods are kept concise in this article. Interested readers can find full details in the above-mentioned articles.…”
Section: Methodology and Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Second-generation indices can be, in general, considered to be superior to firstgeneration triggers owing to a potentially better correlation between the distributed parameters and resulting losses, although the performance ultimately depends on many design considerations. In the case of tsunami losses, for instance, Goda et al (2019) found the forecasting errors in secondgeneration indices were slightly inferior to those for firstgeneration triggers. Progressively, as sensors become more ubiquitous and precise, and as technology facilitates communication of measurements, parametric insurance mechanisms are becoming more widespread.…”
Section: Introductionmentioning
confidence: 96%
“…3, we discuss the conceptualization and the mathematical design of a plausible parametric risk transfer tool leveraging physical descriptors of the eruptive events that are both simulated in the risk model as well as reported by public entities during the course of an actual event. The work draws from efforts carried out in the development of parametric triggers for other perils, fundamentally earthquake (Franco, 2010(Franco, , 2013Goda, 2013Goda, , 2014Pucciano et al, 2017;Franco et al, 2018) and tsunami (Goda et al, 2019). Section 4 applies the framework presented to an application case study in Japan where a regional (or national) entity may desire to adopt this type of risk transfer mechanism to help offset costs associated with ash fall generated by an eruption of Mt Fuji.…”
Section: Introductionmentioning
confidence: 99%